Sonogashira Reactions of 2,3,4,5-Tetrabromofuran: Synthesis of 2,3,4,5-Tetraalkynylfurans, 2,3,5-Trialkynylfurans and 2,5-Dialkynylfurans - Malik, Imran; Ahmad, Zeeshan; Reimann, Sebastian; Nawaz, Muhammed; Patonay, Tamás; Langer, Peter (Synlett, 2012)
2,3,4,5-Tetrabromofuran is transformed into a variety of alkynyl-substituted furans by regioselective Sonogashira cross-coupling reactions. In this context, the first 2,3,4,5-tetraalkynylfurans and 2,3,5-trialkynylfurans were prepared. 2,3,4,5-Tetraalkynylfurans and 2,5-dialkynyl-3,4-diarylfurans show interesting fluorescence properties.
Keywords: catalysis; palladium; Sonogashira reaction; furan; regioselectivity; fluorescence